Interference effects in the H(→ γγ) + 2 jets channel at the LHC - Coradeschi, F. (2015)
We compute the interference between the resonant process pp → H(→ γγ) + 2 jets and the corresponding continuum background at leading order in QCD. For the Higgs signal, we include gluon fusion (GF) and vector boson fusion (VBF) production channels, while for the background we consider all tree-level contributions, including pure EW effects (O(α 4 QED)) and QCD contributions (O(α 2 QEDα 2 s )), plus the loopinduced gluon-initiated process. After convolution with the experimental mass resolution, the main effect of the interference is to shift the position of the mass peak, as in the inclusive GF case studied previously. The apparent mass shift is small in magnitude but strongly dependent on the Higgs width, potentially allowing for a measurement of, or bound on, the width itself. In the H(→ γγ) + 2 jets channel, the VBF and GF contributions generate shifts of opposite signs which largely cancel, depending on the sets of cuts used, to as little as 5 MeV (toward a lower Higgs mass). The small magnitude of the shift makes this channel a good reference mass for measuring the inclusive mass shift of around 60 MeV in the Standard Model.